-z+1=z-1

Simple and best practice solution for -z+1=z-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -z+1=z-1 equation:


Simplifying
-1z + 1 = z + -1

Reorder the terms:
1 + -1z = z + -1

Reorder the terms:
1 + -1z = -1 + z

Solving
1 + -1z = -1 + z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
1 + -1z + -1z = -1 + z + -1z

Combine like terms: -1z + -1z = -2z
1 + -2z = -1 + z + -1z

Combine like terms: z + -1z = 0
1 + -2z = -1 + 0
1 + -2z = -1

Add '-1' to each side of the equation.
1 + -1 + -2z = -1 + -1

Combine like terms: 1 + -1 = 0
0 + -2z = -1 + -1
-2z = -1 + -1

Combine like terms: -1 + -1 = -2
-2z = -2

Divide each side by '-2'.
z = 1

Simplifying
z = 1

See similar equations:

| 0.13x-0.52=1.48x-3.523 | | X^6+8=0 | | (x+9)2-100=0 | | 3x-70=x | | 7x+5(1x+-1)=5+12x | | 7p-3=p+6 | | -5(t-2)+9t=6t-2 | | 4x+5y+7x+3y= | | (x-5)2-16=0 | | 3(4x-8)+1=12x-23 | | k+5=3-w | | 3x=-5y+4 | | -3+2=-10+3x | | 3.6+x=4.9 | | 8.21m=49.26 | | 4x+7=4(x+3) | | (x-2)2=144 | | -6(-7x-5)-2x=-1 | | 61+2x= | | 45+4x= | | -(1+7)-(-7-x)=36 | | -3(7+g)=9 | | 9114=93k | | 5(x-7)-3=-38 | | 3n+(12-5n)=22 | | 2/5-9=4 | | 4x^2-17x+25=3x+4 | | x=18.2-.4y | | (x+6)2=36 | | 6.5(-4)+4=-22 | | 2x-4=(x+10) | | (x+1)2=81 |

Equations solver categories